2017
DOI: 10.15252/emmm.201606690
|View full text |Cite
|
Sign up to set email alerts
|

Sodium permeable and “hypersensitive” TREK ‐1 channels cause ventricular tachycardia

Abstract: In a patient with right ventricular outflow tract (RVOT) tachycardia, we identified a heterozygous point mutation in the selectivity filter of the stretch‐activated K2P potassium channel TREK‐1 (KCNK2 or K2P2.1). This mutation introduces abnormal sodium permeability to TREK‐1. In addition, mutant channels exhibit a hypersensitivity to stretch‐activation, suggesting that the selectivity filter is directly involved in stretch‐induced activation and desensitization. Increased sodium permeability and stretch‐sensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
73
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 68 publications
(75 citation statements)
references
References 42 publications
2
73
0
Order By: Relevance
“…Furthermore, work by Schmidt et al (33) showed that pharmacological inhibition of a K 2p (TASK-1) is a novel potential pharmacological strategy for treatment of chronic atrial fibrillation. Additionally, Decher et al identified a mechanism in a patient whereby increased sodium permeability through a K 2p (TREK-1) predisposed the individual to right ventricular outflow tract ventricular tachycardia (34). Finally, recent work from our laboratory corroborates the notion that K 2p channels are more than simply background leak channels, acting as active participants in ventricular repolarization (35).…”
Section: Introductionsupporting
confidence: 53%
“…Furthermore, work by Schmidt et al (33) showed that pharmacological inhibition of a K 2p (TASK-1) is a novel potential pharmacological strategy for treatment of chronic atrial fibrillation. Additionally, Decher et al identified a mechanism in a patient whereby increased sodium permeability through a K 2p (TREK-1) predisposed the individual to right ventricular outflow tract ventricular tachycardia (34). Finally, recent work from our laboratory corroborates the notion that K 2p channels are more than simply background leak channels, acting as active participants in ventricular repolarization (35).…”
Section: Introductionsupporting
confidence: 53%
“…Statistics were performed as previously described (29). Briefly, every dataset for wild-type and each mutant and for every current/kinetical feature analyzed were tested with a Shapiro-Wilk test for normality.…”
Section: Methodsmentioning
confidence: 99%
“…Some are terminated by Valsalva manoeuvre (50% in one study),12 likely through release of acetylcholine (decreases cAMP (cyclic AMP) concentrations via muscarinic cholinergic receptors) 9 13. Evidence for a somatic mutation increasing sensitivity to sympathetic stimulation of the focus has been reported 14. However, adenosine insensitivity and focal structural abnormalities on cardiac MRI have been reported in some individuals, suggesting that small re-entry circuits or abnormal automaticity may sometimes be a cause 9 15.…”
Section: Non-inherited Vt In Structurally Normal Heartsmentioning
confidence: 99%